Study of Entrepreneurial Capital and Economic Education Aspects in Entrepreneurial Decision Making Food Street Vendors at Losari Beach Area, Makassar City - Andika Isma; Andi Naila Quin Azisah Aliasyahbana (Universitas Negeri Makassar, 2022)
This study aims to determine the entrepreneurial capital and economic education aspects of street vendors at the Losari Beach area of Makassar City. This study uses qualitative methods, using data collection techniques with observation, interviews and documentation. With the data collection techniques above, the educational aspect of street vendors in the Losari Beach area of Makassar City is one of the factors that support entrepreneurial success, with the assumption that better education will provide knowledge of street vendors in managing their business. Meanwhile, in terms of entrepreneurial capital, it shows that the distribution of capital by the government has not been completely evenly distributed to traders in the Losari Beach area and this capital is very important to support the smooth running of the street vendors.